1998
DOI: 10.1007/bf03401725
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Migraine with Aura, Anxiety, and Depression Is Associated with Dopamine D2 Receptor (DRD2) NcoI Alleles

Abstract: These data indicate that MWA, anxiety disorders, and major depression can be components of a distinct clinical syndrome associated with allelic variations within the DRD2 gene. Clinical recognition of this genetically based syndrome has significant diagnostic and therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 52 publications
3
79
0
3
Order By: Relevance
“…Genetic, epidemiologic and clinical data confirm this association [6][7][8][9]. Cephalalgiaphobia can be possibly classified as an anxiety disorder, under the heading of specific phobias, different from other specific phobias.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Genetic, epidemiologic and clinical data confirm this association [6][7][8][9]. Cephalalgiaphobia can be possibly classified as an anxiety disorder, under the heading of specific phobias, different from other specific phobias.…”
Section: Discussionmentioning
confidence: 88%
“…Social phobia is three-fold more common in migraineurs than in controls [8]. Phobias and migraines were linked genetically via the DRD2 dopamine receptor allele [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high platelet levels of dopamine have been observed in migraineurs (D'Andrea et al 2006). Several association studies on D 2 -like receptors and migraine with or without aura have been reported, but with contradictory results (Maude et al 2001;Mochi et al 2003;Peroutka et al 1998;Peroutka et al 1997). Thus, it appears that if dopamine and its receptors are at all involved in the pathophysiology of migraine, the exact mechanism of action still remains unclear.…”
Section: Dopamine Receptorsmentioning
confidence: 99%
“…[9][10][11][12][13][14][22][23][24][25][26] By genotyping about 200 controls and patients with prolactinomas, we found similar allelic frequencies of TaqI A1/A2, TaqI B1/B2, HphI G/T and NcoI C/T in the two groups that were comparable to those of European and American populations (NCBI, Entrez SNP database, TaqI A: http:// www.ncbi.nlm.nih.gov/SNP/snp_ref.cgi?rs ¼ 1800497; TaqI B: http://www.ncbi.nlm.nih.gov/SNP/snp_ref.cgi?rs ¼ 1079597; HphI:…”
Section: Filopanti Et Almentioning
confidence: 99%
“…Due to the critical role of dopaminergic activity in the central nervous system, several studies examined the association between common polymorphisms of the DRD2 gene and behavioral traits, psychiatric and neurological diseases, such as schizophrenia, alcoholism, smoking, opioids and polysubstance abuse, and susceptibility to migraine. [9][10][11][12][13][14] Accordingly, in vivo evidence supporting the potential functional significance of DRD2 variants has been accumulating. In particular, previous studies reported the association of DRD2 TaqI A, TaqI B and NcoI polymorphisms with modifications in D2 receptor binding and expression in human central nervous system, particularly in the striatum.…”
Section: Introductionmentioning
confidence: 99%